MI 4 Name: Mathematical Induction Let’s look at another example, this time something we’ve already seen before. There are often many different ways to prove the same result; here, we will prove that n X k= k=1 n(n + 1) , 2 n≥1 by mathematical induction. The base case is relatively easy. Note that for n = 1, 1 X k=1= k=1 1(2) . 2 Proceeding to the induction step, we first assume that n X k= k=1 We want to show that n+1 X k= k=1 n(n + 1) . 2 (n + 1)(n + 2) . 2 But we have n+1 X k= n X k + (n + 1) k=1 k=1 n(n + 1) +n+1 2 n = (n + 1) +1 2 (n + 1)(n + 2) = . 2 = by assumption Then by mathematical induction, we see that n X k=1 k= n(n + 1) 2 for all n ≥ 1. Induction 1.1 Spring 2010 MI 4 Name: Now here are some to try on your own. 1. Prove that n X k=1 k2 = n(n + 1)(2n + 1) . 6 2. Find the sum of the first n odd integers, beginning at 1, and prove your result using induction. 3. Consider the arithmetic sequence ak = 3k − 2. Using what you have already learned, find the sum n X ak . k=1 Then prove your result is valid using induction. 4. Using what you have already learned, find n X 2k . k=0 Then prove this result is true using induction. Induction 1.2 Spring 2010